The Meaning of the Sakinah Family in Silver Age Wedding in Palembang - Lesi Susanti; Zuhdiyah Zuhdiyah; Fajar Tri Utami (Indonesian Journal of Behavioral Studies, 2022)
This study aims to determine the meaning of the sakinah family at a silver age marriage in the city of Palembang. This research uses qualitative research with a descriptive method. The subjek in this study had six people; the six subjects are married couples, meaning there are three husband and wife couples. Based on the results of this study, it can be concluded that the characteristics of sakinah family in silver age marriages are, the first; have a good communication pattern for fellow family members in other ways, namely taking time to talk together with family. The second; is that mutual respect for one another is fundamental in forming a sakinah family. The third; is openness to the family and mutual trust, establishing good communication and mutual respect for one another.